Inarinsaamen käsitemetaforat - Idström, Anna (Suomalais-ugrilainen Seura, 2010)
This study discusses the conceptual metaphors of Inari Saami, an endangered, indigenous, Finno-Ugrian language spoken in northern Finland. The research focuses on systematical mappings between source and target domains in conventional Inari Saami metaphors and metonymies. The research material consists of the Inarinsaamen idiomisanakirja [Inari Saami idiom dictionary] which has been compiled by the author in collaboration with an Inari Saami co-author; the Inarilappisches Wörterbuch; Inarinsaamelaista kansantietoutta [Inari Saami folk knowledge]; and Aanaarkiela čájttuzeh [Inari Saami sample texts]. The metaphors and metonymies found in these literary sources are divided into categories on the basis of the target domains and according to the classic model of Lakoff ja Johnson (1980). This method reveals the systematical recurrence of source domains inside each category and thus discovers the systematical patterns of metaphoric mapping, the conceptual metaphors . As a result 44 conceptual metaphors and 16 conceptual metonymies are presented through approximately 500 glossed examples. These findings are discussed against the background of what is known about the cognitive and neural processing of metaphors on the one hand, and what is known about Inari Saami culture on the other. This theoretical framework highlights culture as the underlying force behind conceptual metaphors. The recurring metonymies seem to follow a culturally salient indexicality. For example, the Inari Saami conceptual metonymy TIME IS NATURE reflects the seasonal changes in the year s cycle, which was the salient index of time in traditional Inari Saami culture. The recurring metaphors, for their part, follow a culturally salient iconicity. The conceptual metaphor PRIDE IS ANTLERS is based on an iconicity which is experienced and interpreted by the Inari Saami. A proud person is associated with a reindeer who shows off his impressive antlers. The conceptual metaphor/metonymy seems to be a reflection of culture rather than a cognitive means of ...